2022
DOI: 10.1371/journal.pone.0274120
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cytokine detection based on flow cytometry in hemocytes from Galleria mellonella larvae: A new protocol

Abstract: Invertebrates are becoming increasingly popular models for research on the immune system. The innate immunity possessed by insects shows both structural and functional similarity to the resistance displayed by mammals, and many processes occurring in insect hemocytes are similar to those that occur in mammals. However, the use of insects as research models requires the development of methods for working with hemocytes. The aim of this study was to develop a protocol for intracellular cytokine detection in Gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…In contrast with previous reports demonstrating separable sub-populations of fixed Galleria hemocytes based on relative size and internal complexity by flow cytometry [28], we found that live hemocytes, subjected to a minimal processing method, behaved as a single population. Which instead corroborates more recent methods to analyse fixed hemocytes by flow cytometry [27]. Even with the use of 4% PFA (Figure 2A) we failed to observe distinct hemocyte groups based on FSC and SSC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast with previous reports demonstrating separable sub-populations of fixed Galleria hemocytes based on relative size and internal complexity by flow cytometry [28], we found that live hemocytes, subjected to a minimal processing method, behaved as a single population. Which instead corroborates more recent methods to analyse fixed hemocytes by flow cytometry [27]. Even with the use of 4% PFA (Figure 2A) we failed to observe distinct hemocyte groups based on FSC and SSC.…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by the observation that one of the assigned cell gates from that study appears in the same vicinity as our described debris gate - which we have conclusively demonstrated does not contain viable hemocytes (Figure 2 A and B). Further to this, others also report that the use of fixatives, as well as altering centrifugation speed, had an overall effect on cell morphology – as shown by clear differences in the FSC vs SSC scatter plots [27]. However, we do not rule out the possibility that the hemocyte landscape changes developmentally, as the larvae progress towards pupation, possibly resulting in a more complex distribution of cells the onset of metamorphosis [23].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, progress is being made, e.g. in the recent description of intracellular interferon-gamma detection in larval haemocytes (Wrońska et al 2022 ). Detection was based on the cross-reactivity of rabbit monoclonals recognizing human interferon gamma with G. mellonella interferon gamma.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Flow cytometry analysis was performed according to a protocol previously developed by our team for the determination of cytokine-like proteins in insect hemocytes ( 28 ). The hemolymph taken from both untreated and fungus-treated larvae was centrifuged (400xg, 10 min) and washed with PBS.…”
Section: Methodsmentioning
confidence: 99%